Nutritional enrichment from Bali sardinella (Sardinella lemuru) head meal in fish crackers as emergency food: Pengayaan nutrisi dari tepung kepala lemuru (Sardinella lemuru) pada fish crackers sebagai pangan darurat - Mutamimah, Dewi; Arista, Yuvita Lira Vesti; Untari, Dewi; Liasari, Ade (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Various natural disasters occur frequently in Indonesia, such as heavy floods, tornadoes, landslides, volcanic eruptions, earthquakes, and tsunamis, which disrupt access to the facilities and infrastructure necessary for clothing and food needs. Emergency food is an essential alternative for victims of natural disasters because of its long shelf-life and high nutritional content. Crackers are classified as emergency foods because of their ease of transport and extended storage period. The aim of this study was to determine the optimal concentration of Bali sardinella head flour based on the nutritional characteristics of fish crackers as a food source. The method used was a completely randomized design with five treatments varying with the addition of Bali sardinella head meal: 0, 5, 10, 15, and 20%.  Data were analyzed using analysis of variance (ANOVA) and a color reader for color analysis. The best results were in 5% of Bali sardinella head flour in fish crackers by proximate analysis with protein, lipid, moisture, ash, and carbohydrate was 4.93±0.46bc, 12.81±0.25d, 11.43±0.59b, 5.19±0.59b, 65.64±0.99a, for dietary fiber was 4.03±0.01b, color properties consist of Lightness (L) 58.15±0.07d, A 11.00±0.00, B 27.15±0.07.  This study provides valuable insights into the nutritional composition of Bali sardinella head meal in fish crackers.